Pengaruh Harga Pokok Produksi Dengan Metode Harga Pokok Pesanan Terhadap Peningkatan Akurasi Laba - Leatemia, Senda Yunita; Basuki, Ferry Hendro (Universitas Muhammadiyah Metro, 2024)
This research aims to empirically test the effect of determining the cost of production using the order cost method on increasing profit accuracy. This research is quantitative research and the data used is primary data collected using a questionnaire. The sample in this research is MSMEs in Ambon City. The results of this research prove that determining the cost of production using the ordered cost method has an effect on increasing profit accuracy and suggestions from this research are for MSME’s players to carry out periodic evaluations so that the cost price determination can be implemented properly so that profit accuracy in MSMEs becomes better.